Program Pengembangan Kompetensi Guru PGTK untuk Meningkatkan Kemampuan Membaca Siswa dengan Metode Jolly Phonics - Herdina Indrijati; Endah Mastuti; Rhajiv Nur Ilham (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2023)
Lately, problems related to pupils’ reading skill at school is increasing. So, teachers have to give more attention to the addressed problems. This study aims to examine the effectivity of the training for kindergarten teacher to uplift pupils’ reading skill through the jolly phonics method. This study involved 29 participants who work as kindergarten teacher in Jember. The training consisted of the presentation from experts, group discussion, role play, pre-test, and post-test. Data was analyzed using Wilcoxon Signed Ranks Test to examine the score difference before and after the training was implemented. Result shows that there is significant increasement (p=0,000) of the participants’ score after the training was implemented. Result of this study could be used as additional reference for implementing jolly phonics method to increase reading skill of the pupils at school.